KONSTRUKSI LITERASI DIGITAL PADA PEMILU 2024 UNTUK MEMBENDUNG ARUS INFORMASI DAN BERITA PALSU - iskandar, dudi; Suratno, Geri; Raharjo, Didik Hariyadi (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
The 2024 General Election will be held on February 14th, 2024. As this nation's most significant political agenda, all groups are involved in the 2014 General Election. Because of this, there is expected to be a discourse battle in every election involving political actors, the mass media, and the public. Not only do information and news form positive discourse, but negative discourse also spreads. The public, candidates, and state actors color the public media space with clear information and good news and salt it with dirty information. Hoax on social media in media and fake news among the masses in the 2024 general election threaten social cohesion and national integration, as happened in the 2014 and 2019 general elections. There must be efforts to stem the spread of hoax and fake news. One of them is digital literacy, including digital media literacy. This research aims to analyze the construction of digital literacy, including digital media, in the 2024 general election to stem hoax and fake news in the 2024 general election. This research uses a qualitative approach with data collection techniques through observation, interviews, and library data. The research results show that, firstly, the election moment is a time that is prone to the circulation of hoax and fake news. This is where digital literacy skills, including digital media literacy, emerge. Second, at a macro level, the state is responsible for digital literacy programs, including digital media literacy. Third, public communication between the Ministry of Communication and Information and the community is a vital bridge that must continue to be maintained and improve its effectiveness and efficiency so that the state's role in building digital literacy, including digital media literacy, is realized as quickly as possible.